Tunable diode effect in a superconducting tunnel junction with biharmonic drive - David Scheer; Rubén Seoane Souto; Fabian Hassler; Jeroen Danon (New Journal of Physics)
A Josephson diode is a superconducting circuit element that enables non-reciprocal transport, allowing a dissipationless supercurrent to preferentially flow in a single direction. Existing methods for achieving the required symmetry breaking mostly rely on specifically-designed materials or carefully-engineered circuits composed of multiple Josephson junctions. Here, we investigate the diode effect induced by applying a biharmonic drive to a conventional superconducting tunnel-junction. In the slow-driving regime, the effect is straightforward to understand in a simple adiabatic picture, providing insight in the tunability of the magnitude and directionality of the diode effect through the drive parameters. We then focus on the fast-driving regime, where we show how the more complex physics underlying the dynamics of the junction can be approximated as a cascaded two-tone mixing process. We derive analytic expressions for the diode efficiency as a function of drive parameters in the limit of small driving amplitudes.